PN code acquisition method based on prepositive 3-order correlated detection - HAO Yan-ling; DENG Zhi-xin; WANG Wei (Tongxin xuebao)
To increase the detection probability of long period PN（pseudo noise） code and decrease its acquisition time, a new method of 3-order correlated detection was proposed, that is, before the synchronization of pseudo random sequence, the chip phase should be synchronized firstly according to the characteristic of 3-order correlation of the PN code and additive white Gauss noise. Theoretical analysis and the results of simulation show that this method can effectively increase the detection probability and decrease the acquisition time.